PENGEMBANGAN MULTIMUDIA PEMBELAJARAN BERBASIS MICROLEARNING UNTUK MENINGKATKAN LITERASI ANAK USIA DINI - Wiwik Adinda; Amat Hidayat; Dewi Cahyaningrat; Sella Oktania; Sohri Ramadhan Alfikri; Beni Junedi (Cakrawala Pedagogik, 2024)
Literacy development in early childhood is an important part of basic education. Microlearning, which presents learning material in short and focused form, can be one solution to increase children's interest and understanding of literacy. This research aims to develop microlearning-based learning media that is effective in increasing early childhood literacy. The research method used is research and development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. This research was conducted at TKIT Nusantara Banten, the subjects in this research were children aged 4-6 years. The research results show that microlearning-based learning media can significantly improve children's literacy skills compared to conventional learning methods. Thus, microlearning can be used as an effective alternative learning method for young children.